2006
DOI: 10.1109/tns.2006.872501
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the developments and improvements of a treatment planning system for BNCT

Abstract: Boron Neutron Capture Therapy (BNCT) is a radiation therapy for cancer that employs a neutron beam and a 10 B-loaded drug to selectively kill tumor cells whilst sparing surrounding healthy tissues (HT). In conventional radiation therapy, treatment planning systems (TPSs) implementing simplified models of radiation transport and dose deposition allow to efficiently optimize all the relevant parameters prior to the patient's irradiation. This simplified approach is not feasible in BNCT, because the presence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the remaining events, 7 Li is emitted in the ground state with no c ray emission, which can be ignored from a dosimetry perspective, although they are frequently utilized for 10 B analysis purposes. [21][22][23] In this project, the authors have shown that an epithermal and thermal neutron field required by BNCT and radioisotope production, respectively, can be realized when a proton of 300 lA at 30 MeV by cyclotron is used.…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining events, 7 Li is emitted in the ground state with no c ray emission, which can be ignored from a dosimetry perspective, although they are frequently utilized for 10 B analysis purposes. [21][22][23] In this project, the authors have shown that an epithermal and thermal neutron field required by BNCT and radioisotope production, respectively, can be realized when a proton of 300 lA at 30 MeV by cyclotron is used.…”
Section: Introductionmentioning
confidence: 99%
“…Tsukuba Plan [10,11] developed by a team including researchers from the University of Tsukuba, is another MC-based TPS [12] utilized PHITS [13] as MC engine. An original prototype software CARONTE [14] and BDTPS are both PET-based TPS, featured a pre-processed module for processing PET images for in vivo boron distribution [15]. NeuCure [16] is a TPS designed especially for BNCT, which developed by Sumitomo Heavy Industries, must be used in combination with another radiotherapy treatment planning product RayStation for image processing.…”
mentioning
confidence: 99%